Membuat Ruangan Bebas Covid 19 Dengan Robot Disinfektan Dibawah Kendali Smartphone - Sitompul, Jonariando; HUTAURUK, SINDAK; Siahaan, Sahat S.P (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2022)
Watering with a robot that uses a nozzle (sprayer) as a device for sprinklers, such as a disinfectant sprayer. To operate this tool, it is controlled using a smartphone to drive a DC pump so that the disinfectant liquid comes out through the nozzle. The disinfectant spraying robot is designed using two DC motors (primary movers) and one DC pump (liquid sprayer) based on an Atmega 8 microcontroller which is controlled by the user via a smartphone with the help of a Bluetooth network. The results of the system test are wireless communication designs to control the robot using a Bluetooth network, namely by installing a bluetooth adapter on the robot so that the robot can receive commands from the user via a smartphone. Watering using 500 ml liquid media, capable of running to spray in the rooms that want to be sprayed with an operating time of 3-5 hours. The movement speed of the robot is 5.3 km/h, the system can rotate 360o and forward, backward, right and left. The nozzle on this robot has a maximum spray distance of 2 meters. From the results of this test, the robot's response is in accordance with what is expected